DESIGN AND IMPLEMENT A TRANSPARENT INTERNET PROTOCOLPACKETS COMPRESSION SYSTEM - Hadi, Suha; Barjas, Firas (Iraqi Journal of Science, 2024)
The data compression process is an important aspect that should be given a goodattention when dealing with slow computer networks. This paper introduces the designand implementation of a transparent compression system that can be utilized byMicrosoft Windows to compress data exchanged among the computers through a LocalArea Network (LAN). On each machine, this system transparently intercepts outgoing IPpackets and compresses them. As well as it will transparently intercept incomingcompressed IP packets and decompresses them.